Application of oral nutritional supplements in patients with colorectal cancer - Liu Yong; Sun Yiming; Yang Ning; Bo Wanlan (结直肠肛门外科)
The incidence of malnutrition is high among patients with colorectal cancer, which directly affects their clinical outcomes, including increased postoperative complications, prolonged hospital stays, higher hospital costs, and reduced tolerance to chemotherapy and radiotherapy, ultimately impacting their survival time. Oral Nutritional Supplements (ONS) refer to the intake of special medical-purpose (formulated) foods in addition to normal food, to compensate for dietary deficiencies. ONS is suitable for colorectal cancer patients with nutritional risk at all treatment stages. This paper reviews the current status of ONS application in colorectal cancer patients before and after surgery, during chemoradiotherapy, and during home care, aiming to provide a reference for enhancing the status and standardization of ONS in the treatment of colorectal cancer patients.